2021
DOI: 10.5194/acp-2021-782
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring DMS oxidation and implications for global aerosol radiative forcing

Abstract: Abstract. Aerosol indirect radiative forcing (IRF), which characterizes how aerosols alter cloud formation and properties, is very sensitive to the preindustrial (PI) aerosol burden. Dimethyl sulfide (DMS), emitted from the ocean, is a dominant natural precursor of non-sea-salt sulfate in the PI and pristine present-day (PD) atmospheres. Here we revisit the atmospheric oxidation chemistry of DMS, particularly under pristine conditions, and its impact on aerosol IRF. Based on previous laboratory studies, we exp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…low occurrence of OH radicals and/or meteorological factors. This hypothesis is supported by the higher importance of OHinitiated DMS oxidation at lower latitudes in the study by Fung et al (2022), and the DMS conversion yields of MSA and HPMTF in the different model runs by Wollesen de Jonge et al ( 2021), where the HPMTF/MSA ratio was considerably lower in the AtmMain case compared to cases with higher temperature and lower RH. This could be both due to differing sources and sinks, such as dry/wet deposition of MSA (Bergin et al, 1995) and HPMTF (Khan et al, 2021), heterogeneous oxidation of MSA (g) (Mungall et al, 2018) and evaporation of MSA from the particle-to the gas phase (Baccarini et al, 2021).…”
Section: Gas-phase Dms Oxidation Productsmentioning
confidence: 56%
See 2 more Smart Citations
“…low occurrence of OH radicals and/or meteorological factors. This hypothesis is supported by the higher importance of OHinitiated DMS oxidation at lower latitudes in the study by Fung et al (2022), and the DMS conversion yields of MSA and HPMTF in the different model runs by Wollesen de Jonge et al ( 2021), where the HPMTF/MSA ratio was considerably lower in the AtmMain case compared to cases with higher temperature and lower RH. This could be both due to differing sources and sinks, such as dry/wet deposition of MSA (Bergin et al, 1995) and HPMTF (Khan et al, 2021), heterogeneous oxidation of MSA (g) (Mungall et al, 2018) and evaporation of MSA from the particle-to the gas phase (Baccarini et al, 2021).…”
Section: Gas-phase Dms Oxidation Productsmentioning
confidence: 56%
“…1) during these months (Berndt et al, 2019;R. Wu et al, 2015), despite the low occurrence of this mechanism compared to the addition pathway in the Nordic Seas according to Fung et al (2022). However, the discrepancies that exist in the relative temporal evolution between measured MSA (g) and HPMTF (g) in summer could also be a sign that HPMTF is not produced as efficiently as MSA close to Svalbard due to e.g.…”
Section: Gas-phase Dms Oxidation Productsmentioning
confidence: 90%
See 1 more Smart Citation
“…17,18 Non-sea salt sulfate can also be formed through the oxidation of dimethyl sulfide (DMS), emitted from the ocean, and contribute to a larger fraction of sulfate in marine aerosol. 19,20 Coastal and estuarine plants can emit VOCs that form organic acids, including formate and acetate. 21−23 Another major natural, terrestrial source of particles is mineral and soil dust, which can be identified through the presence of calcium and carbonate.…”
Section: Introductionmentioning
confidence: 99%